Основные тенденции развития инновационной сферы ЕС - Иванова, Л.Г.; Хаирова, Э.А. (Культура народов Причерноморья, 2013)
Cтатья посвящена исследованию особенностей инновационного развития ЕС, специфики
наднационального стратегического управления научно-технологическим развитием. Рассмотрению
структуры государственного финансирования общих программ НИОКР в странах Европы.
Исследованию особенностей инновационного сотрудничества среди региональных экономических
интеграционных объединений. Выявлению приоритетности реализации инновационных программ ЕС.
Основных направлений сотрудничества Украина-ЕС в инновационной сфере. Стаття присвячена дослідженню особливостей інноваційного розвитку ЄС, специфіки
наднаціонального стратегічного управління науково-технологічним розвитком. Розгляду структури
державного фінансування спільних програм НДДКР у країнах Європи. Дослідженню особливостей
інноваційного співробітництва серед регіональних економічних інтеграційних об'єднань. Виявленню
пріоритетності реалізації інноваційних програм ЄС. Основних напрямів співпраці Україна-ЄС в
інноваційній сфері. The article is devoted to the study of peculiarities of innovative development of the EU, the nature of
supranational strategic management of scientific-technological development. Examination of the structure of
state funding of public R & d programmes in Europe. The study of peculiarities of innovative cooperation among
the regional integration associations. Identification of priority implementation of innovative programmes of the
EU. Peculiarities of the ongoing Seventh framework Programme (FP7) ES, which is the main financial
instrument of the European Union for the support of international cooperation at the scientific and research
activities in almost all scientific fields. Review of the structural organization of the alleged thematic priorities in
Technological platform in the framework Programme FP7. The Main aims of the EU Ukraine cooperation in the
innovation sphere.